Pengarusutamaan Pengurangan Resiko Bencana (PRB) Berbasis Kurikulum Pendidikan Agama Islam - Rubaidi Rubaidi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This paper thoroughly discusses the role of Islamic education institutions in Disaster Risk Reduction (DRR). This field-based research paper takes the locus of MIN Jejeran, Pleret, Bantul, Yogyakarta. The program adapted from Kemendiknas policies takes “Sekolah Siaga Bencana” as the theme. In the midst of disaster phenomena in various regions in Indonesia, MIN Jejeran not only plays an active role in DRR conceptually in the form of integration of Islamic Religious Education (PAI) curriculum, but also increases the level of action in the field. This paper limits only photographing the Earthquake of PRB integration effort into the PAI curriculum to international recognition. This reseach contributes the role of Islamic educational institution to the disaster risk reduction.